Area Studies at the Modern University: Experience in Studying International Communication Strategies - O. A. Nesterova; O. L. Solodkova (Moscow Polytechnic University, 2019)
In this paper, we show the importance of including the large corpus of scholarly, popular and media texts describing the experience of 20th-century Russian and Soviet Indologists in bachelor's Asian studies programmes. We explain the significance of the practical work of Soviet Asian scholars on developing and implementing international communication strategies and practices and show that this work is topical and relevant for modern tertiary education. We emphasize the extensive experience accumulated by Russian Indologists in developing scenarios and models of interaction between Russia and Asian countries that take regional particularities into account. We examine the work of the Russian Indologist, scholar, journalist, publicist and professor Leonid Mitrokhin (1934-2002), winner of the Nehru Award (1985), who worked for over a decade in India and devoted his entire life to studying South and Central Asia. We analyse Leonid Mitrokhin's key communicative practices, whose results are reflected in his monographs, popular books and articles. The results of our linguocultural study confirm the effectiveness of the implementation of friendly communication strategies in Indo-Soviet relations in the 1960s and 1970s. The case study of Leonid Mitrokhin's work shows the broad range of professional competencies of Soviet Indologists, who had in-depth knowledge of the political and sociocultural makeup of South Asia, the systemic connections between individual social, economic and political groups and institutes, and the ethnopsychological, ethnocultural and religious particularities of interethnic communication. The knowledge and skills of Soviet Indologists allowed them to make accurate forecasts of the development of the political and economic situation in South Asia and neighbouring regions, promote communication, make expert assessments in key areas of interaction between the USSR and countries in the region, elaborate effective communication strategies, and shape a positive image of their country in the international arena. The study of the communication experience of Soviet Indologists shall help contemporary students to learn the methodology of area studies, develop their strategic thinking, expand their study and research interests, improve their knowledge of the region's history and interregional relations, and learn the basics of foreign impact strategies and the practice of foreign propaganda in Asia.